1999
DOI: 10.1080/014198799329495
|View full text |Cite
|
Sign up to set email alerts
|

From Hermano Lejano to Hermano Mayor: the dialectics of Salvadoran transnationalism

Abstract: A dialectical framework is proposed for analysing the economic and political practices associated with immigrant transnationalism. The causes and consequences of the transnational relations sustained by Salvadoran migrants in Los Angeles and Washington, DC, with El Salvador is used to test this proposition. It is argued that the conditions of Salvadorans' exit from their country of origin and of their reception in the US explains their tendency to invest considerable resources in forging and maintaining transn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
0
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(153 citation statements)
references
References 2 publications
1
135
0
17
Order By: Relevance
“…To date, research has focused predominantly upon developing nations and the potential role of diaspora networks in advancing the development process within their homelands, especially in relation to skilled labour migration and financial remittances (Kuznetsov, 2006;Solimano, 2008), At the level of cities, there has been only limited research into the economic role of diaspora networks. Different types of transnational businesses which develop as diaspora communities are established and become embedded, have been identified (Landolt et al, 1999;Pécoud, 2002;Portes et al, 2002). Research has also demonstrated the various ways that diaspora networks support the development of such business activity in terms of providing resources, knowledge and information and markets opportunities (Bagwell, 2008;Kitching et al, 2009;Portes et al, 2002 and link areas of labour supply with demand through informal and formal recruitment and brokerage activities (Poros, 2001).…”
Section: Diaspora Relations and Business Networkmentioning
confidence: 99%
“…To date, research has focused predominantly upon developing nations and the potential role of diaspora networks in advancing the development process within their homelands, especially in relation to skilled labour migration and financial remittances (Kuznetsov, 2006;Solimano, 2008), At the level of cities, there has been only limited research into the economic role of diaspora networks. Different types of transnational businesses which develop as diaspora communities are established and become embedded, have been identified (Landolt et al, 1999;Pécoud, 2002;Portes et al, 2002). Research has also demonstrated the various ways that diaspora networks support the development of such business activity in terms of providing resources, knowledge and information and markets opportunities (Bagwell, 2008;Kitching et al, 2009;Portes et al, 2002 and link areas of labour supply with demand through informal and formal recruitment and brokerage activities (Poros, 2001).…”
Section: Diaspora Relations and Business Networkmentioning
confidence: 99%
“…Recognising that transnational entrepreneurship comes in a variety of different shapes and sizes, Landolt et al (1999) developed a typology based on a study of transnational business ventures found within the El Salvadoran immigrant communities of Los Angeles and Washington DC. The typology is based on identifying whether the key production inputs to an enterprise (i.e.…”
Section: Transnationalism Amongst Ethnic Minority Businessesmentioning
confidence: 99%
“…Evidence from studies of Dominican and Salvadoran immigrants do suggest that premigration experiences shape new country adaptation and transnational engagement. Only after experiencing homeland economic crises did a significant number of immigrants from these countries send remittances (Menjivar, 2000: 100;Landolt, Autler and Baires, 1999;Itzigsohn, Cabral, Medina and Vázquez, 1999). There also is evidence that diverse waves of immigrants from other countries experiencing social revolutions, namely Vietnam (Shelley, 2001), China (Kuhn, 2008;Pieke, Nyiri, Thuno and Ceccagno, 2004), and Poland (Erdmans 1998), relate differently to their homeland from their new land, with differences traceable to distinctive premigration experiences.…”
Section: Resultsmentioning
confidence: 99%